Cervantes global - Ramírez Santacruz, Francisco; Sánchez Jiménez, Antonio (Ediciones de Iberoamericana, 2022)
The global nature of Cervantes Global´s work is evident in the worldwide distribution of its readers, in the variety of methodologies from which it is studied and in the depth of the texts, which are attractive in any cultural context. Cervantes Global illustrates the heterogeneous and dialectical nature of Cervantism with contributions from various countries: Germany, Argentina, Canada, South Korea, Spain, United States, France, Israel, Italy and Switzerland. The volume brings together different but complementary approaches and methodologies that allow establishing a dialogue between different notions and critical categories, as well as promoting a self-reflective and self-critical attitude within Cervantism. The volume contains works on the reception of Don Quixote, but also studies on its female figures, on the equestrian theme, on the canon of Cervantine kings, or on the ideal of the Christian knight. Likewise, it presents studies on other Cervantine works (Exemplary Novels, Persiles), providing a global vision of it.